Interactive Learning Media for Early Childhood Education through Android-Based Educational Games using GDLC Method - Lendy Rahmadi; M. Junius Effendi; Muhammad Said Hasibuan (LPPM Universitas Islam 45 Bekasi, 2025)
The rapid development of technology has influenced various aspects of life, including education. One of the innovations in the field of education is the use of technology-based learning media, such as interactive multimedia, which can enhance students' interest in learning. This research aims to develop an Android-based educational game called Edufun Kids Game, using the Game Development Life Cycle method. (GDLC). This game is designed to help early childhood children recognize letters, numbers, animals, and fruits interactively, creating a fun learning atmosphere and making it easier for educators to deliver the material. The research was conducted at the Tunas Ilmu Early Childhood Education in Pagar Alam City, where the previous learning media was still conventional. The implementation of the Edufun Kids Game shows positive results in increasing children's learning motivation and facilitating a more effective teaching and learning process, as evidenced by beta testing results where 85% of respondents rated the game as helpful for preschoolers in recognizing numbers, letters, animals, and fruits. The use of Android technology allows this application to be easily accessed on mobile devices, providing flexibility for users. The development of Android-based educational games can be an innovative solution to improve the quality of early childhood education